Legal and Regulatory Studies for the Downstream of Manufacturing of Walking Aids for the Blind - Sukapto, Paulus; Fauzan, Bagus (Ann Publisher, 2026)
Background. The Indonesian government, through President Joko Widodo, has been promoting downstream for Indonesian industries since 2020. Starting from mineral and mineral products, video games to medical devices. This research discusses specifically for medical devices, namely, the downstream development of road aids for people with visual disabilities based on sensor technology, which is an important innovation in supporting user mobility, safety, and independence. In fact, the success of the downstream of these innovations is not only determined by technical and functional aspects, but also depends on legal readiness and compliance with applicable regulations in accordance with the mandate of article 1 paragraph (3) of the 1945 Constitution, that '.. Indonesia is a State of Law..'. Purpose. This article aims to comprehensively examine the legal and regulatory frameworks governing the manufacturing system to ensure compliance with applicable laws and regulations for the downstream production of road aids for people with visual disabilities in Indonesia. Some of the aspects studied include intellectual property rights, technical and commercial licensing, quality standards and certifications, and the mapping of legal risks in the downstream process of innovation. Method. The research method used is socio-legal, where the analysis techniques are a mix of qualitative and quantitative through legal literature studies, field observations, multidisciplinary focus group discussions (FGDs), market surveys, and in-depth interviews with key stakeholders. Data were analyzed to assess the level of legal readiness and identify potential legal barriers that could affect the mass production and distribution of blind disability walkers. Results. The results of the study show that although there has been an initial foundation in the form of a patent certificate as a basis for judicial protection, various legal loopholes and risks are still found, including the lack of trademark registration, the inconsistency of the legality of business entities and business classification, the incomplete licensing of the distribution of medical devices, and the lack of optimal fulfillment of quality standards and legal documentation. This condition may hinder commercialization and downstream funding if not addressed comprehensively. Conclusion. This study recommends preparing an integrated legal and regulatory roadmap as a prerequisite for downstreaming the innovation of blind-disabled road aids. Implementation. A comprehensive socio-legal approach is expected to provide certainty and legal protection for inventors and partners, while ensuring the safety and rights of people with visual disabilities as consumers.